2020
DOI: 10.1038/s41598-020-63979-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term potentiation prevents ketamine-induced aberrant neurophysiological dynamics in the hippocampus-prefrontal cortex pathway in vivo

Abstract: N-methyl-D-aspartate receptor (NMDAr) antagonists such as ketamine (KET) produce psychotic-like behavior in both humans and animal models. NMDAr hypofunction affects normal oscillatory dynamics and synaptic plasticity in key brain regions related to schizophrenia, particularly in the hippocampus and the prefrontal cortex. It has been shown that prior long-term potentiation (LTP) occluded the increase of synaptic efficacy in the hippocampus-prefrontal cortex pathway induced by MK-801, a noncompetitive NMDAr ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 94 publications
1
14
0
Order By: Relevance
“…In addition, we have recently shown that distinct coupling occurs between the HPC-mPFC during each state. In the deactivated state, we observed a coherence peak in the 0.5-2 Hz band, with the mPFC leading the HPC, while in the activated state, there was a peak in theta with the HPC leading the mPFC and a time lag consistent to data of freely-moving animals (Lopes-Aguiar et al, 2020). We also showed that mAChR activation by pilocarpine dose-dependently increased activated over deactivated states (Lopes-Aguiar et al, 2013).…”
Section: Functional Connectivitysupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, we have recently shown that distinct coupling occurs between the HPC-mPFC during each state. In the deactivated state, we observed a coherence peak in the 0.5-2 Hz band, with the mPFC leading the HPC, while in the activated state, there was a peak in theta with the HPC leading the mPFC and a time lag consistent to data of freely-moving animals (Lopes-Aguiar et al, 2020). We also showed that mAChR activation by pilocarpine dose-dependently increased activated over deactivated states (Lopes-Aguiar et al, 2013).…”
Section: Functional Connectivitysupporting
confidence: 78%
“…While juvenile mice exhibited elevated cortical excitability in an uncoordinated manner relative to the HPC, adult mice showed weaker evoked potentials in mPFC and increased LTD, suggesting impaired functional connectivity during adulthood. In iHPC-mPFC, ketamine-induced aberrant oscillatory coupling in mPFC and alterations in the HPC-PFC synaptic efficacy ( Lopes-Aguiar et al, 2020 ). The authors demonstrated that prior induction of LTP in the CA1-mPFC attenuates these effects, highlighting the importance of high-frequency stimulation as a non-pharmacological alternative strategy to investigate HPC-PFC modulation and help in the prevention or attenuation of cognitive impairments in schizophrenia.…”
Section: Hippocampus-prefrontal Cortex Neuromodulation In Cognition and Animal Models Of Neuropsychiatric Disordersmentioning
confidence: 99%
“…This pattern of gamma modulation is also observed under urethane anesthesia, which is characterized by cyclic alternations between cortical states that resemble NREM sleep oscillations (deactivated states) and REM sleep oscillations (activated states) (Clement et al, 2008). Systemic administration of ketamine alters the cyclic alternations between deactivated and activated states, and the coupling between delta and gamma oscillations in the mPFC in urethane anesthetized rats (Lopes-Aguiar et al, 2020). Importantly, PV inhibition is suggested to regulate state transitions (Zucca et al, 2017).…”
Section: Introductionmentioning
confidence: 79%
“…S1D, E). Urethane anesthesia is a validated model for testing of mechanistic hypotheses regarding sleep-like brain oscillations (Hauer et al, 2019), and has been particularly employed for investigation of the effects of NMDAR antagonists on oscillatory patterns in different brain circuits (Kiss et al, 2013;Lopes-Aguiar et al, 2020). Use of an anesthetized preparation circumvents the increases in gamma power associated with hyperlocomotion elicited by administration of NMDAR antagonists in awake mice (Hakami et al, 2009).…”
Section: S1a-c)mentioning
confidence: 99%
See 1 more Smart Citation